Sustainable Future for Human Security Environment and Resources (Springer Singapore, 2018)
This book focuses on the environmental components of sustainability, including aspects of resourcing and the environmental impacts of human societies. Marine and tropical forest ecosystems, food security and other natural resources, as well as technologies for the environmental control of societal impacts are examined. This volume is multi-disciplinary, but with a consistent focus on the natural environment. This 2-volume set discusses a wide range of topics concerning sustainability and human security in Asia, particularly South East Asia. The individual chapters have been contributed by authors from various fields, and due to the breadth of the material are separated into two thematic volumes.The set offers a valuable resource for professionals and researchers in the urban planning industry, postgraduates, policymakers, government officials and natural resources managers. In addition, it can be used in courses on Environmental Engineering, Agriculture and Forest ry, Public Policy and Earth Science.